Modeling by disruption and a selected‐for partner for the nude locus. (28th December 2020) - Li, Jian; Lee, Yun‐Kyoung; Fu, Wenyu; Whalen, Anne M; Estable, Mario C; Raftery, Laurel A; White, Kristin; Weiner, Lorin; Brissette, Janice L
Abstract: A long‐standing problem in biology is how to dissect traits for which no tractable model exists. Here, we screen for genes like the nude locus ( Foxn1 )—genes central to mammalian hair and thymus development—using animals that never evolved hair, thymi, or Foxn1 . Fruit flies are morphologically disrupted by the FOXN1 transcription factor and rescued by weak reductions in fly gene function, revealing molecules that potently synergize with FOXN1 to effect dramatic, chaotic change. Strong synergy/effectivity in flies is expected to reflect strong selection/functionality (purpose) in mammals; the more disruptive a molecular interaction is in alien contexts (flies), the more beneficial it will be in its natural, formative contexts (mammals). The approach identifies Aff4 as the first nude‐like locus, as murine AFF4 and FOXN1 cooperatively induce similar cutaneous/thymic phenotypes, similar gene expression programs, and the same step of transcription, pre‐initiation complex formation. These AFF4 functions are unexpected, as AFF4 also serves as a scaffold in common transcriptional‐elongation complexes. Most likely, the approach works because an interaction's power to disrupt is the inevitable consequence of its selected‐for power to benefit. SYNOPSIS: This study reports a simple way to dissect the molecular basis of traits when the traits evolved in organisms difficult to study. The approach identifies selected‐for interactions, the molecular interactions shaped and preserved by positive selection during trait evolution, and here uncovers an essential transcriptional activator of a uniquely mammalian developmental mechanism. The selected‐for (most beneficial) interactions of mammalian molecules can be revealed via the molecules' most disruptive interactions in fruit flies, i.e., the interactions most synergistic and effective at inflicting harm. A genetic screen of flies for drivers of hair and thymus development in mammals identifies AFF4, a novel driver of hair and thymus development in mammals, providing proof of principle. The study's approach, flash‐forward genetics, turns tractable species into models for the evolutionary novelties of other lineages, in a sense inducing a "flash‐forward" along another evolutionary path. Abstract : A genetic screen in Drosophila for genes that synergize with mammalian FOXN1 identifies Aff4 as a nude‐like locus. AFF4 cooperates with FOXN1 in mammalian hair and thymus development.